PENGARUH PENGETAHUAN, PERSEPSI EFEKTIVITAS, KUALITAS PELAYANAN, TRANSPARANSI DAN KESADARAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK - Pitriani; Baihaqi (UNIB Press, 2022)
The purpose of the research was to analyze the influence of the knowledge of tax, effectivity of tax perception, service quality of tax officers, transparency and awareness of taxpayers toward compliance of corporate taxpayer in Bengkulu City. The sample corporate taxpayer in Bengkulu City which taken by accidental sampling. The samplings are 143 respondents. The method of the data analysis used multiple regression analysis. The results from the data analysis showed that: (1) the knowledge of tax have positive and significant effect toward compliance of corporate taxpayers; (2) the effectivity of tax payer have positive and significant effect toward compliance of corporate taxpayers; (3) the service quality of tax officers have positive and significant effect toward compliance of corporate taxpayers; (4) transparency of tax have positive and significant effect toward compliance of corporate taxpayers; and (5) the awareness of taxpayers have positive and significant effect toward compliance of corporate taxpayers.